Measurement and Improvement of Employee Engagement Level , a study case in PT Dirgantara Indonesia (Persero) - Purba, Sondang Romian; Gustomo, Aurik (The Indonesian Journal of Business Administration, 2014)
Abstract— The high turn over rate  in  Directorate of Technology and Development and the  high overtime rate in the Directorate of Production in PT Dirgantara Indonesia are few circumstances that show the need of improvement in  employee engagement level.  The study is to measure and analyze the  employee engagement and give recommendation to improve the employee engagement level in PT Dirgantara Indonesia. The survey in this study will use the WIFI model, that will show how the employees think about the Wellbeing, Information, Fairness and Involvement dimensions in the company. The study was conducted using both qualitative nd quantitative methods. Qualitative methods were in-depth interviews and focus group discussion with selected employees, and the questionnaire is the one designed based on the questionnaire from Sarah Cook using the WIFI Model.  The results of the survey shows the most significant area to improve the level of employe engagement in PT Dirgantara Indonesia is Involvement Dimension.  To produce the atmosphere of involvement and encouraging the employee to get involved in PT Dirgantara Indonesia,  the sense of involvement need to happen at three levels. The first level is involvement with employee’s direct line that can be improved by the action of coaching and facilitating and empowering skills. The second level is involvement with other team,  consist of encouraging cross functional involvement. And the third level is Involvement with organization as a whole, that consist of the activity of making senior manager as Role Models.  Keywords: Employee Engagement, WIFI Model, Involvement